ԶԼՄ-ների անկախության և ազատության արդի հիմնախնդիրները - Լ. Ա. Խառատյան (ՀՀ ԳԱԱ հրատ.)
Вопросы, связанные со свободой и независимостью СМИ, основаны на двух принципах: невмешательство государственной власти в деятельность СМИ, в сферу упорядочения их деятельности и коллегиальности органов, занимающихся регулированием названных процессов с учетом сопряженных с этим политических и социальных моментов. Из этого следует, что СМИ являются не институтом власти, а институтом общества, призванным представлять интересы общества, его запросы,контролировать власть и содействовать общенациональному развитию. The issues, related to the freedom and independence of the media are based on two principles: non-interference of state authorities in the activities of the media, in the regulation of their activities and the collegiality of the bodies that carry out this regulation, taking into account the largest part of the political and social aspects. This means that the media are not the source of power, but the institution of society, called upon to represent the interests and the request of society, to control the power and to promote the nation-wide development.
Keywords: Law; Language and Literature; PNJ Journalism; The periodical Press, etc